The usefulness of ground-penetrating radar images for the research of a large sand-bed braided river: case study from the Vistula River (central Poland) - Lejzerowicz, Anna; Kowalczyk, Sebastian; Wysocka, Anna (Geologos, 2014)
Ground-penetrating radar (GPR) surveys and sedimentological outcrop analyses were combined in order to determine the reflection patterns and internal architecture of terrace deposits of the Vistula River at Kępa Zawadowska in the southern part of Warsaw (central Poland). The sedimentary analyses concerned the granulometric composition and lithofacies analysis. The 34 GPR profiles, which were obtained in two outcrops, using a Malå RAMAC/GPR system with 500-MHz and 250-MHz shielded antennas, were up to 100 m long. The most characteristic ground-penetrating radar profiles are presented; they show a high-resolution data set of radar facies. The GPR data suggest the presence of three geophysically different units, namely with high-angle inclined reflections (radar facies 1), with discontinuous undulating or trough-shaped reflections (radar facies 2), and with low-angle reflections (radar facies 3). The internal structure of the fluvial deposits was obtained by integration of the GPR and sedimentological data, which combination provides a more accurate visualisation of sedimentary units than do reconstructions that are based only on standard lithologic point data.